P6.09 Identifying the barriers sex workers experience to participate in policy making decisions in johannesburg, south africa. (8th July 2017) - Mienies, Keith; Surgey, Gavin
Abstract : Introduction: The basis of a democratic government is consultation and participation by its citizenry in public policy making. Marginalised populations don't have the power and authority due to a lack of agency and a variety of factors. These factors in combination with socio-economic challenges cripple their rights to healthcare policies that is realistic with their needs. Are sex workers able to participate in policy making in South Africa? And what hinders their participation in the policy making decisions. By having a better understanding of the barriers to participation in the policy making process, we are more readily able to address these barriers for an inclusive consultation of sex workers in future policy work. Methods: This is a qualitative study conducted in South Africa using grounded theory.Data from informants who currently are or have been involved in policy making are collected as well as focus group discussions with sex workers. Informants were asked a series of questions relating to legislation that governs participation in policy making, participation and consultation platforms available to sex workers, social exclusion and stigma experienced by sex workers, the impact of knowledge and education on the ability to participate, agency (political, human and social), the impact of organisation/mobilisation on participation, identifying their perceived barriers to participation and how to strengthen participation of sex workers in public policy making institutions. Results and conclusion: The barriers identified by both sex workers and key informants to participation of sex workers in policy making includes: Stigma of sex workers; Time away from income earning activities Criminalization of sex work The political interests of development aid providers The internal locus of control of sex workers Lack of political support